(untitled) (Medico Legal Update, 2020)
Web-based formative assessment tools have become widely recognized education as valuable resources for self-directed learning. Introducing Google forms for simultaneous assessment of first year subjects in MBBS students is a time saving acceptable approach. Objectives: To introduce a simultaneous online web based assessment tool (Google forms) for first year MBBS students. To evaluate the perception and attitude of the first MBBS students towards the assessment tool (Google forms). Method: 122 first year medical students were informed about an simultaneous one sitting test 4 days prior for the introductory topics in Anatomy, Physiology and Biochemistry. A web page link was shared with the students in their google account and student were asked to reply to the 45 questions asked in the google form. The performance of the students were analyzed in the spread sheet. After completion of the test student were asked to fill 20 questions feedback form each questions were based on Likert scale to evaluate their attitude and perception towards the online assessment of Anatomy, Physiology and biochemistry at a single sitting. The feedback questionnaire was analyzed. Results: On analyzing the feedback questionnaire it was shown 75 % of students felt answering in google forms are fairer and 65% felt its better than pen and paper assessment. 79% of the students had trust in google forms as they felt cheating cannot be easily done in this tool. 68% of the students felt marking is more accurate in this tool. On analyzing the performance of the students it is seen, 61.4 % of the students were above 50% of the total score out of which 27.04% of the students scored more than 75% . Only 16% of the students were below the 25% of total score. This study thus showed, students were interested in using the new tool in assessing their knowledge and they too wanted to use the link for revising their subject in future..